ESL speak and smile: e-kit version 2.0 / Raja Nur Hidayah Raja Yacob ... [et.al.] - Raja Yacob, Raja Nur Hidayah; Ab Ghani, Mohd Azizi; Mohamad, Mimi Mazlina; Mohd Salleh, Salwani; Awang, Nur Amalina (Universiti Teknologi MARA, Kedah, 2023)
Blended learning, combining online and face-to-face instruction, has become the norm in the current educational landscape. As students undergo a return of traditional classrooms apart from the virtual ones, non-native speakers experience speaking anxiety when delivering oral presentations. The fear of speaking in front of audiences can cause nervousness and adversely affect their performance. To address this concern, an e-kit has been developed with the aim of bolstering the confidence of second language learners and equipping them with strategies to alleviate speaking anxiety. The comprehensive e-kit encompasses an array of valuable resources tailored to support students in their oral presentations. The e-kit offers commonly used phrases for delivering effective oral presentations, detailed presentation criteria to provide guidance, samples of public speaking videos that exemplify best practices, and the invaluable opportunity for students to receive expert feedback. Notably, this interactive e-kit enables students to upload their videos for instant comments from qualified instructors. Alternatively, they can engage in peer-review activities facilitated by a comprehensive checklist. Educators and instructors who have incorporated the e-kit into their teaching methodologies have reported notable improvements in students' presentation skills. Students who have utilized the e-kit demonstrate greater ease and confidence when delivering their presentations, ultimately leading to higher academic performance compared to their counterparts without access to this valuable resource. This e-kit is highly recommended for tertiary students aiming to overcome speaking anxiety in English. It can be easily purchased by scanning a QR code. Its value and effectiveness suggest it should be widely commercialized and introduced to schools in the future. The targeted audiences are hoped to empower themselves by overcoming their speaking anxiety, especially in English Language.